Mechanism of chromatin remodelling revealed by the Snf2-nucleosome structure - Liu, Xiaoyu; Li, Meijing; Xia, Xian; Li, Xueming; Chen, Zhucheng (Nature (London), 2017)
Chromatin remodellers are helicase-like, ATP-dependent enzymes that alter chromatin structure and nucleosome positions to allow regulatory proteins access to DNA. Here we report the cryo-electron microscopy structure of chromatin remodeller Switch/sucrose non-fermentable (SWI2/SNF2) from Saccharomyces cerevisiae bound to the nucleosome. The structure shows that the two core domains of Snf2 are realigned upon nucleosome binding, suggesting activation of the enzyme. The core domains contact each other through two induced Brace helices, which are crucial for coupling ATP hydrolysis to chromatin remodelling. Snf2 binds to the phosphate backbones of one DNA gyre of the nucleosome mainly through its helicase motifs within the major domain cleft, suggesting a conserved mechanism of substrate engagement across different remodellers. Snf2 contacts the second DNA gyre via a positively charged surface, providing a mechanism to anchor the remodeller at a fixed position of the nucleosome. Snf2 locally deforms nucleosomal DNA at the site of binding, priming the substrate for the remodelling reaction. Together, these findings provide mechanistic insights into chromatin remodelling. The cryo-electron microscopy structure of Saccharomyces cerevisiae Snf2 chromatin remodeller bound to a nucleosome and a proposed mechanism for DNA translocation by Snf2 are presented. Structure of a chromatin remodeller Chromatin remodellers are helicase-like, ATP-dependent enzymes that alter chromatin structure and nucleosome positions in order to allow regulatory proteins access to DNA. Here, Zhucheng Chen and colleagues report the cryo-electron microscopy structure of the budding yeast Snf2 chromatin remodeller bound to a nucleosome and propose a mechanism for DNA translocation by Snf2. The remodeller interacts with the nucleosome mainly using helicase motifs and binds the phosphate backbones along the DNA minor groove. Most of the DNA-binding elements within Snf2 are conserved across other families of remodelling enzymes, indicating that this mode of nucleosome engagement is likely to be widespread.